Three-year growth hormone treatment in short children with X-linked hypophosphatemic rickets: effects on linear growth and body disproportion - Živičnjak, Miro; Schnabel, D.; Staude, H.; Even, G.; Marx, M.; Beetz, R.; Holder, M.; Billing, Heiko; Fischer, D.-C.; Rabl, W.; Schumacher, M.; Hiort, O.; et al. (The journal of clinical endocrinology & metabolism, 2011)
Children with X-linked hypophosphatemic rickets (XLH) are prone to progressive disproportionate stunting despite oral phosphate and vitamin D treatment.Our objective was to analyze the effects of GH treatment on stature and lengths of linear body segments in short children with XLH.A 3-yr randomized controlled open-label GH study in short prepubertal children with XLH (n = 16) on phosphate and calcitriol treatment was conducted. A cohort of XLH patients (n = 76) on conservative treatment served as an XLH reference population.Changes in sd scores (SDS) of stature and linear body segments, i.e. sitting height, leg and arm length, and sitting height index (i.e. ratio between sitting height and stature) were the main outcome measures.XLH patients presented at time of enrollment with significant impairments of stature (−3.3 SDS) and linear body segments compared with healthy children. Leg length (−3.8 SDS) was most impaired, whereas sitting height (−1.7 SDS) was best preserved. The markedly elevated mean sitting height index (+3.3 SDS) reflected severe body disproportion. GH resulted in a sustained increase in linear growth (stature, +1.1 SDS; sitting height, +1.3 SDS; leg length, +0.8 SDS; arm length, +1.1 SDS; each P < 0.05 vs. baseline), whereas no significant changes were observed in controls. Mean height SDS at 3 yr did not significantly differ between groups. Sitting height index remained stable in both the GH-treated patients and in study controls but increased further in the XLH-reference population.The 3-yr GH treatment improved linear growth without progression of body disproportion in short children with XLH.
Gesehen am 23.01.2023